Exogenous Insulin Effect on the Initiation of Breast Cancer in Type 2 Diabetes Mellitus Patients - Hassan, Hanan H.; Saif ullah , Perry H. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Growing evidence has indicated that women with type 2 diabetes mellitus are at an increased risk of developing breast cancer. However, as a major adjuvant treatment, the influence of hormone therapy such as exogenous insulin on type 2 diabetes mellitus in primary breast-cancer remains controversial. Objective: To explore the relationship between different types of hypoglycemic medications for diabetes and the factors that may contribute to the initiation of breast cancer.Methods: The study included 80 blood samples taken from 80 females recruited from Ibn Al-Bitar Center for Cardiac Surgery Hospital in Baghdad, Iraq, between November 2022 and February 2023. They were within the age range of 40 to 70 years. They were divided into three groups according to the treatment strategy and duration of disease as follows: Group 1: (20) patients who take insulin only, Group 2: (20) patients who take metformin with insulin, and G 3: (40) patients on metformin only for less than one year. An enzymatic oxidation technique was used to test the following biochemical parameters for all research groups: Total cholesterol, triglycerides, fasting blood glucose, and high-density lipoprotein cholesterol. Using the Friedewald formula, the very low-density lipoprotein cholesterol and low-density lipoprotein cholesterol were determined. Using an enzymatic process, Insulin levels and Insulin like growth factor-1(IGF-1), Estrogen receptor alpha (ERα) levels, and breast cancer susceptibility protein 1 (BRCA1) were measured with an enzyme-linked immunosorbent assay (ELISA). Glycated hemoglobin (HbA1c) level was measured with a sandwich immunodetection method. Finally, The Homeostasis Model Assessment for insulin resistance (HOMA-IR) was calculated according to the specific formula.Results: The values for HbA1C%, FBS, and lipid profile showed non-significant differences when compared between study groups. While BRCA-1, estrogen receptor alpha (ERα), insulin, insulin growth factor IGF-1, and HOMA IR All showed significant differences among all groups.Conclusion: Taking metformin only for less than one year seemed to contribute to higher levels of BRCA-1.